Leadership and legacy : the Presidency of Barack Obama - Lansford, Tom; Brattebo, Douglas M.; Watson, Robert P., 1962-; Funderburk, Casey Maugh (SUNY series on the presidency., 2021)
"Applies a variety of scholarly approaches to analyze the long-term impact of President Obama as a leader and policymaker"--